Enterprise resource planning system implementation and success measurement : case study of a small to medium sized enterprise - Shaikh, N. (Cranfield University, 2014)
It is widely believed that major financial benefits can be achieved by organisations implementing Enterprise Resource Planning software. It is also believed that such systems are a time consuming and a costly endeavour which can result in loss of resource and eventually failure of implementation. Furthermore not all companies have the technical competence or financial stability to take such a risk. Alternatively companies can be more modular in their approach in implementing such solutions, adopting one module at a time: the one that suits them best according to their financial and technical situation and so gradually work towards Enterprise Resource Planning implementation. A measurement technique is also required to track progress, success and failure of such a process. As global trade routes become more affordable and the cost of shipping becomes marginalised compared to the overall cost of a product there is a direct impact on Small to Medium sized enterprises as they start competing with global businesses and not just locally. Enterprise Resource Planning or ERP's are one of the many tools that a company can utilise to enhance its efficiency and become more competitive however implementing such a technology is an expensive and risky undertaking. This thesis aims to outline the systems and technologies that a SME can utilise to achieve such a goal using open-source software infrastructure while reducing the expenses and risk involved. It also points out a more “one step at a time” approach to such implementations, hinting that you implement only what you can afford in terms of time and resource and then build towards a bigger system when time and cash prevails hence having a gradual improvement to the overall ecosystem. The observations derived in this paper are outputs of implementation of such technologies at a local SME acting as the case study. Results show that although such an approach can be helpful in bringing the development cost down, continuous efforts in improving the system and on-going systems support is required for the post-implementation phase to have a positive impact on the performance of the company.
Keywords: Streamline Business Processes; Enterprise Resource Planning; ERP2